Exploring Finnish upper secondary English teachers’ cognition and practice of teaching intercultural competence - Zheng, Huanhuan (2018)
Nowadays, globalization has increased the interaction and encounters between diverse cultures, which makes intercultural competence increasingly imperative in multicultural situations. Students are the masters of the future world, as are the English teachers, who play a principle role in students’ development (Polat & Ogay, 2014). It is therefore vital to consider the current situation of intercultural competence’s teaching, and what are the possible ways to cultivate and promote students’ intercultural competence. The aim of the study is to explore Finnish upper secondary English teachers’ cognition and practice of teaching intercultural competence. The dataset includes recordings of teacher interviews and videos of classroom teaching from four English teachers from the same Finnish senior high school have been transcribed and observed. The main focus of the analysis is concerning the questions of where intercultural issues are presented and how they are incorporated into classroom practice, with the extracts or key moments taken out for further analysis. Using Borg’s theory of teacher cognition, it is found that though teachers seek to teach intercultural competence, theses attempts are quite limited due to the influence of their previous experience of learning and teaching, and the contextual factors mostly for textbooks design and matriculation exams. Moreover, teachers’ practices which incorporate intercultural competence were selected and analyzed based on Byram’s model of intercultural competence consisting of knowledge, skills, attitudes and critical cultural awareness(Byram, 1997). Accordingly, suggestions on how to teach intercultural competence are concluded and put forward which might support future teaching.